Developing a policy based algorithm for mobile devices to access neighboring Wi-Fi APs in enterprise environment - Noor, Riashad; Billah, Muhammad Mutasim; Md. Ashraful Alam; Abu Nayeem Md. Mustakim (BRAC University, 2017)
Cataloged from PDF version of thesis report.